PENGARUH POLA KEMITRAAN TERHADAP PENDAPATAN PETANI TEBU - Analia Utami; Dinar Dinar; Kosasih Sumantri (UNIVERSITAS MAJALENGKA, 2016)
The Issues in this research is about the effect of partnership system on cane farmers income at PT PG Rajawali II, PG Jatitujuh Unit, Majalengka with 53 cane farmer respondents. This reseach used some questionnaire as a data collection tool, and was done by using simple random sampling. This research used descriptive method with data collection through field observations and some questionnaire. Data obtained were processed by simple linear regression on SPSS software for Windows 21st version. The reseach showed that the partnership model are applied in PG Rajawali II PG Jatitujuh unit is intiplasma partnership system. This partnership system can increase the income of cane farmers dan get the positive effect on the income of sugar cane farmers by 54%. The conclusion in this reseach is cane farmers' incomes can be affected by the partnership system. Key words : Partnership System, Cane Farmers